2022
DOI: 10.1002/ejp.1905
|View full text |Cite
|
Sign up to set email alerts
|

Systematic reviews do not (yet) represent the ‘gold standard’ of evidence: A position paper

Abstract: The low quality of included trials, insufficient rigour in review methodology, ignorance of key pain issues, small size, and over-optimistic judgements about the direction and magnitude of treatment effects all devalue systematic reviews, supposedly the 'gold standard' of evidence. Available evidence indicates that almost all systematic reviews in the published literature contain fatal flaws likely to make their conclusions incorrect and misleading. Only 3 in every 100 systematic reviews are deemed to have ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Despite these limitations, we hope that our systematic review has met the items outlined by Moore et al (2022) to consider when reading a systematic review of efficacy of interventions for pain.…”
Section: Potential Biases In the Review (Limitations And Strengths)mentioning
confidence: 99%
“…Despite these limitations, we hope that our systematic review has met the items outlined by Moore et al (2022) to consider when reading a systematic review of efficacy of interventions for pain.…”
Section: Potential Biases In the Review (Limitations And Strengths)mentioning
confidence: 99%
“…Apart from the cohort of Bean et al, the included studies suffered from several biases, and their quality was globally poor. As recently stated., the small number of participants in several studies significantly decreases the confidence in their results (Moore et al, 2022). Furthermore, the results from cross‐sectional studies (Bean et al, 2016b; Dumas et al, 2011) should be read with caution.…”
Section: Discussionmentioning
confidence: 99%
“…The other meta‐analysis showed that MT reduces pain with a larger effect size ( I 2 = 82%; standardized mean difference = −0.81; 95% CI = −1.36 to −0.25; p = 0.005) compared with other methods (Wang et al, 2021 ). However, the conclusion of these meta‐analyses are subject of debate due to questionable methodological and statistical choices: the use of fixed‐effect analyses (Borenstein et al, 2010 ), the inclusion of low‐powered and poor‐quality studies, the strong heterogeneity and the interpretation of non‐clinically relevant effects (Moore et al, 2022 ). Furthermore, no systematic review has evaluated MT impact on the patients' quality of life and disability.…”
Section: Introductionmentioning
confidence: 99%